Investigation and Research on Food Safety Knowledge, Attitude and Behavior of University Students in Kunming Based on Big Data Analysis. Issue 2 (October 2020) - Zhang, Chunsheng; Liu, Rui; Zhang, Linyu; Dong, Liangfei
Abstract: This article uses questionnaire surveys, combined with computer big data analysis, to study the food safety knowledge, attitudes and behaviors of college students in Kunming. The results show that the awareness rate of safety knowledge of the respondents is low, and their attitude and behavior need to be improved. It is necessary for colleges and universities to carry out food safety publicity and education in various ways, to help college students establish a positive and correct attitude towards food safety, and to guide college students to develop good food safety behavior habits.